2016
DOI: 10.1007/s11146-016-9557-0
|View full text |Cite
|
Sign up to set email alerts
|

Do Investors Infer Vocal Cues from CEOs During Quarterly REIT Conference Calls?

Abstract: We examine the investor reaction to emotionally charged information. Using audio files of quarterly earnings conference calls and specialized Layered Voice Analysis software, we isolate the emotional content of managers' vocal cues. With results that are both statistically and economically significant, we find that executive emotion is positively related to investors' initial reaction. Moreover, this strong investor reaction to emotional signals by REIT managers appears to be justified, suggesting that credibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 41 publications
0
15
0
Order By: Relevance
“…Mayew and Venkatachalam (2012) showed that investors react to managers’ vocal cues in a pattern that picked up cumulative abnormal returns around the conference calls; those returns extended out six months. Price et al (2016) found that investors appear to overreact to managers’ emotional vocal cues in the conference calls, whereas there is a rapid correction to this short run overreaction.…”
Section: Investors’ Emotion Literaturementioning
confidence: 95%
See 2 more Smart Citations
“…Mayew and Venkatachalam (2012) showed that investors react to managers’ vocal cues in a pattern that picked up cumulative abnormal returns around the conference calls; those returns extended out six months. Price et al (2016) found that investors appear to overreact to managers’ emotional vocal cues in the conference calls, whereas there is a rapid correction to this short run overreaction.…”
Section: Investors’ Emotion Literaturementioning
confidence: 95%
“…Kuhnen and Knutson (2011) find that positive emotional states motivate investors to take risky investment portfolios, while negative emotional states hinder them to do so. In two different studies, Mayew and Venkatachalam (2012) and Price et al (2016) utilized the layered voice analysis platform to isolate CEOs' vocal cues in their earnings conference calls. The research pairs also tested the investors' reactions to CEOs' vocal cues.…”
Section: Investors' Emotion Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…Only recently, have researchers focused on textual sentiment in the context of the real estate market. For example, Doran et al (2012) and Price et al (2017) analyze transcripts and audio files of earnings conference calls for a REIT sample, to show that sentiment impacts initial reaction-window abnormal returns. In creating a custom dictionary for the real estate domain, Ruscheinsky et al (2018) find media sentiment to lead future REIT market movements.…”
Section: Related Literature and Hypothesis Developmentmentioning
confidence: 99%
“…Consequently, in order to take advantage of growth opportunities, US REITs must turn to the capital markets. As such, US REIT managers have an unusually strong incentive to be transparent and maintain investor trust (Danielsen et al , 2009; Doran et al , 2012; Price et al , 2017). Third, the underlying assets of US REITs are real estate, which is an illiquid, slow-moving asset and thus more compatible to analysis over a relatively large time span (e.g.…”
Section: Introductionmentioning
confidence: 99%